The pursuit of lifelong participation: the role of professional football clubs in the delivery of physical education and school sport in England. (3rd March 2016) - Parnell, Daniel; Buxton, Sarah; Hewitt, Des; Reeves, Matthew J.; Cope, Ed; Bailey, Richard
Abstract : Physical Education and School Sport (PESS) offers a key vehicle to support the development of lifelong participation in children and young people. At a time of government cuts and the emergence of external providers, including professional football clubs, it is pertinent to explore current practice. This research set out to explore the delivery, and partnerships involved within the School Sports Premium, particularly the relationship between the community arms and registered charities of professional football clubs and schools to deliver PESS. Semi-structured interviews with community managers from football community programmes and head teachers revealed two key themes; partnership working and the role of the community coach. Findings suggest the need to develop the scope of the partnership and to build methods of evaluation to understand the impact of the coaches' practice in schools. Further evaluation of the partnerships between professional football clubs and schools would bring an increased understanding of the effectiveness and impact of the partnerships, in order to improve practice and the subsequent effectiveness of PESS, in terms of its contribution towards lifelong participation for children and young people.